Experiences and perceptions on the quality of higher education student halls of residence: The perspective of displaced students - Saleiro, S.; Mauritti, R; Justino, E.; Silva, S. F. da; Belchior-Rocha, H.; Pintassilgo, S. (EDULEARN24 Proceedings, 2024)
In Portugal, the process of broadening the social base for access to higher education observed over the years has favoured the democratization of the system. However, this process also highlights the weaknesses associated with a shortage of public and private housing units administered by institutions to accommodate displaced students, including an increasingly heterogeneous group of international students. Inadequate response to lack of student accommodation is particularly exacerbated in large cities where the conversion of a significant number of private housing units to short-term rentals for tourists has decreased available housing for a rising inflow of students. For students displaced from their usual place of residence during the academic period, the challenges of adaptation and integration to a new stage of schooling are compounded by the need to find decent housing within a price range consistent with their socio-economic background, suited to their circumstances and daily routine, and located close to their educational institution. This paper aims to share the experiences and perceptions of students regarding the quality and running of student accommodation in public higher education in Portugal managed by Ação Social Escolar, a government programme that offers financial support to students from impoverished families. In substantive terms, the analysis uses data from the National Survey of Displaced Students, as well as information obtained in focus groups with representative structures of these students (CIES-Iscte, 2023 - ERASMUS+ Residences Study). The analysis reveals some difficulties in managing common spaces, but also reflects a positive assessment in most of the categories of analysis, such as location, mobility and the conditions and services available. In general, the perceptions of students who live in these accommodations (or those who represent them) show a preference for the transition from the old dormitory model of residence, which still includes a considerable proportion of the residences currently available, to a new and more open, collaborative and convivial model of residence. This implies, among other things, an investment in the common spaces and outdoor spaces of the residences, as well as more flexible rules for the appropriation of space by residents and others in the community.